Development of StoryMaps-Based Learning Media on Tourism Resource Materials of Batu City from a Spatial Perspective - Mia Ayu Maulidya; Purwanto Purwanto; Maria Cicilia Tri Palupi (Jurnal Inovasi Pendidikan dan Sains, 2025)
The innovation of digital learning media is needed in line with the continuous advancement of technology. The utilization of geospatial technology must be enhanced to promote students’ spatial literacy through the habituation of thinking from a spatial perspective. This study aims to develop a feasible StoryMaps-based learning media for the Tourism Resources material analyzed from a spatial perspective. This study is classified as Research and Development (R&D), using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and eval__uation. The media was developed by integrating multimedia elements such as maps, photos, videos, animations, graphics, and virtual tours, which were systematically, interactively, and communicatively packaged using the ArcGIS Online StoryMaps platform. The developed learning media were tested through a demonstration in a limited-scale trial. The research instrument used was a questionnaire to measure the feasibility and user satisfaction levels of the learning media. The results of the study showed that the average feasibility score of the StoryMaps-based learning media from two validators, namely one media expert and one subject matter expert, was 88.8% with a classification of highly feasible. The trial results of the StoryMaps-based learning media obtained a score of 95.0% from the teacher and 91.3% from the students, classified as highly satisfactory. Based on these results, the StoryMaps learning media is considered feasible for use in the learning process